Recent English borrowings in the language of young Poles - Bloch-Rozmej, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
People have always borrowed what they needed, both things and words. Language contact has launched a plethora of different phenomena, of which word borrowing seems to be a conspicuous and very influential process. This article is intended to delve into the problem of English loan words in the language of young people in Poland. We shall establish the most recent contributions to Polish that are regularly used by young people and point out the channels through which borrowings enter the language. Further, some light will be shed on the frequent forms of adaptation loans undergo. Finally, young people’s attitudes towards borrowings will be presented as well as the influence of loan word usage on the process of communication

Głównym celem artykułu jest analiza jednego z najważniejszych zjawisk związanych z kontaktem językowym - zagadnienia zapożyczeń językowych. W centrum uwagi znajdują się najnowsze zapożyczenia z języka angielskiego w komunikacji polskiej młodzieży. Materiał badawczy został pozyskany za pomocą ankiety internetowej, w której wzięło udział 76 osób w wieku od 15 do 30 lat, głównie studentów lubelskich uczelni wyższych. Zebrane dane pozwoliły na ustalenie listy najczęściej używanych anglicyzmów, motywacji dla ich stosowania oraz zbadanie wpływu na komunikację młodych ludzi. Analizie poddano także wskazane przez respondentów adaptacje, jakim podlegają te wyrazy we współczesnej polszczyźnie
Najnowsze zapożyczenia angielskie w języku młodych Polaków
Keywords: English; borrowing; language contact; communication; young people’s speech; język angielski; zapożyczenia; kontakt językowy; komunikacja; język młodzieży